The Effect of Education on Prevention of Stunting on the Knowledge of Pregnant Women at the Sei Dadap Health Center, Sei Dadap District, Asahan Regency in 2022 - Juita Sari; Suhartini Suhartini (Sean Institute, 2023)
Stunting or often called stunting or shortness based on Umar (2017) said that the condition of failure to thrive in children under five years old (toddlers) is due to chronic malnutrition and repeated infections, especially in the first 1,000 Days of Life (HPK) period. This study aims to determine the effect of education on stunting prevention on the knowledge of pregnant women at the Sei Dadap Health Center, Sei Dadap District, Asahan Regency in 2022. The research method used The type of research used was quasi-experimental research. The research location was conducted at the Sei Dadap Health Center, Sei Dadap District, Asahan Regency. The time of the study was July-October 2022. The sample in this study were all pregnant women who came to the Sei Dadap Health Center, Sei Dadap District, Asahan Regency, totaling 30 respondents. The sample used was purposive sampling. The research instrument is a questionnaire that has been tested for validity and reliability. The results showed that 30 respondents had statistical test results using the paired t test where the average knowledge score in the pre-test with no treatment was 11.40, whereas after the knowledge treatment with Education about Stunting Prevention had an average knowledge score in post test is 12.97, meaning that it can be concluded that knowledge with education about stunting prevention after treatment can increase respondents' knowledge about stunting. The conclusion that can be obtained is that knowledge with education about after treatment can increase respondents' knowledge about stunting prevention at the Sei Dadap Health Center in 2022. It is suggested that this research will add information in the development of science, especially in midwifery in studying the importance of stunting prevention..